2009
DOI: 10.1177/0963662508098684
|View full text |Cite
|
Sign up to set email alerts
|

Seeing satellite data

Abstract: Complex scientific visualizations are becoming standard parts of many educational experiences, both in and out of schools. We found that satellite visualizations used by ocean scientists were difficult for teachers, students, and museum visitors to understand. The research reported on here documents some of those difficulties and explores alternate visualizations that proved more robust for novice users of the data. Five different visualizations of two ocean properties as sensed by satellites are shown and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 5 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…That this color scheme was the default in eight out of nine visualization toolkits studied by Borland and Taylor (2007) helps to affirm its prominence. The rainbow color scale has become so entrenched that it even has been associated with perceived scientific authenticity among the public (Phipps and Rowe 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That this color scheme was the default in eight out of nine visualization toolkits studied by Borland and Taylor (2007) helps to affirm its prominence. The rainbow color scale has become so entrenched that it even has been associated with perceived scientific authenticity among the public (Phipps and Rowe 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another issue arises when yellow is located on the middle of the scale. As the brightest and most vibrant color, yellow also is the most attention-getting [American Meteorological Society (AMS) 1993;Silva et al 2007;Phipps and Rowe 2010]. Because of this nature, yellow is best used to emphasize diverging values (Light and Bartlein 2004), which often is not the case in familiar uses of the rainbow scale.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that students at all levels struggle with constructing and interpreting visualizations of data, whether in the form of simple graphs and tables [40,41] or more sophisticated false-color imagery such as that used in geospatial visualization of remotely sensed data [42]. Moreover, students have significant difficulties connecting elements of visualizations and models with the real-world phenomena they represent, even when those data and models are keyed to geospatial representations which offer a degree of familiarity and cultural resonance [42][43][44][45][46]. Research has explored the integration of computing technologies and visualizations of data with inquiry teaching practices as a way of addressing data literacy for both students [13,20,47,48] and teachers [21,42].…”
Section: Integration Of Data Literacy In K-12-stem Programsmentioning
confidence: 99%
“…Museums with their unique objects and collections have the potential to be sites par excellence for learning to observe, for looking closely, systematically noticing, comparing and contrasting, while trying out different forms of reasoning about what is seen. But engaging and supporting powerful forms of visual observation is tricky, with a potentially steep learning curve that makes success in an unmediated context challenging (Eberbach and Crowley ; Phipps and Rowe ). Enabling everyday observers to move toward seeing (and coming to know) with the eyes of science requires explicit educational scaffolding and mediation (Eberbach and Crowley ).…”
Section: Scaffolding Scientific Observationmentioning
confidence: 99%